2020
DOI: 10.1177/0003702820908352
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy: An Exploratory Study to Identify Post-Radiation Cell Survival

Abstract: Resistance to radiotherapy has been an impediment in the treatment of cancer, and the inability to detect it at an early stage further exacerbates the prognosis. We have assessed the feasibility of Raman spectroscopy as a rapid assay for predicting radiosensitivity of cancer cells in comparison to the conventional biological assays. Cell lines derived from breast adenocarcinoma (MCF7), gingivobuccal squamous cell carcinoma (ITOC-03), and human embryonic kidney (HEK293) were subjected to varying doses of ionizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…In previous research, RS has demonstrated the potential to be incorporated into radiation therapy as a label-free technique to reveal the biochemical dynamics and assess the treatment response for various types of cancer. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] Nevertheless, conventional unsupervised dimension reduction techniques can provide limited resolution in distinguishing responses from different chemicals. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] In this manuscript, the GBR-NMF-RF-SHAP data analytical framework has demonstrated an outstanding capability to resolve signals such as radiation response and hypoxia indicators corresponding to constrained chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, RS has demonstrated the potential to be incorporated into radiation therapy as a label-free technique to reveal the biochemical dynamics and assess the treatment response for various types of cancer. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] Nevertheless, conventional unsupervised dimension reduction techniques can provide limited resolution in distinguishing responses from different chemicals. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] In this manuscript, the GBR-NMF-RF-SHAP data analytical framework has demonstrated an outstanding capability to resolve signals such as radiation response and hypoxia indicators corresponding to constrained chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][59][60][61][62][63] Nevertheless, conventional unsupervised dimension reduction techniques can provide limited resolution in distinguishing responses from different chemicals. [9][10][11][12][13][14][15][16][17][59][60][61][62][63] In this manuscript, the GBR-NMF-RF-SHAP data analytical framework has demonstrated an outstanding capability to resolve signals such as radiation response and hypoxia indicators corresponding to constrained chemicals. Moreover, GBR-NMF-RF-SHAP also exhibited efficiency in analyses across various types of cancer data (cell and tissue).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that in the absence of Ku80 protein, there is a significant increase γH2AX foci, a marker of DSBs, in knockout cells [34]. We analyzed not reach the level induced by 2 Gy of IR which was reported to result in more than 70% survival using a colony forming assay in HEK293 cells [35]. These findings lead us to conclude that it is not the accumulation of DSBs that is the driving factor behind the loss of cell viability in Ku70 knockout cells.…”
Section: Examination Of γH2ax Repair Foci Accumulation In Ku70 Knocko...mentioning
confidence: 90%
“…RS enables sample archiving and retesting for more precise therapy response assessment. The advantages of RS maps have been harnessed to quantify dynamic changes at the single-cell level in terms of sensitivity, for spatial and temporal resolution of multiplexed metabolic changes, and for quantitative analysis [ 64 , 68 ].…”
Section: Living Sample Viability Measurement Methodsmentioning
confidence: 99%